Investment crisis: causes and ways to overcome - Kishchenko , T. (Ways to Improve Construction Efficiency, 2020)
The article considers the main features and peculiarities of the investment crisis, which is an element of the systemic crisis that has gripped the state economy and negatively affects all spheres of public life and activity. The investment crisis is an obstacle to operational, investment and financial activities of construction companies, causing demand for real estate. The global internal causes of low investment activity are analyzed, which are, first of all, the current state of the state economy, which increases investment risk and significantly complicates the formation of investment programs, creates conditions for illegal withdrawal of investment resources from the real economy to other areas. All this is a consequence of insufficiently deep development of regulatory and legal framework for the development of investment activities in the country: the existing legal norms do not work, there is no effective mechanism of punishment and property liability for improper use of investment resources, and the result - violation of the investment process. Among the identified and the ways of overcoming the investment crisis mentioned in the article are as follows: renewal of domestic sources of investment resources in the real economy, which were paralyzed in the last years of the country's life, the need to strengthen strong incentives and arguments for returning lost domestic capital from abroad. The creation of new laws on the efficient use of own sources to finance domestic investments in the modernization of production and introduction of new, modern technologies, as well as laws that will prevent the outflow of capital from the state during the acute investment crisis. The lack of a clear legal framework and non-compliance with current legislation is the main reason for the significant reduction in investment in Ukraine, both domestic and foreign.